The Effect of Using Special Exercises on Developing the Speed Endurance and Achievement of the 400m Freestyle Run for Students preparatory Stage (Damu Journal of Sport Sciences, 2025)
The 400m run is of great importance because it is considered one of the most powerful runs in track and field events, requiring a high degree of speed, endurance, and strength. The 400m race is also considered a race in which running or sprinting is performed at a high speed, less than the maximum. Hence, the importance of the research lies in the use of this proposed approach, which develops the speed endurance of the 400m run for fourth-year preparatory students, given that this age group is close to that of junior athletes. Furthermore, the physical structure and growth of students at this stage are receptive to all physiological changes that occur to the body from... As a result of the loading programs in the exercises they apply, the research problem emerged from studying the level of speed endurance in the 400m freestyle event for juniors and its importance in developing the study of this phenomenon among students. This phenomenon requires focus from the coach and athlete in implementing the given training modules. Furthermore, the characteristic of speed endurance is considered the backbone of achieving good performance in the 400m race. It was noted that it is not possible for junior runners, as well as student competitors, to continue from the end of the race to the end at the desired level. This indicates a deficiency in the characteristic of speed endurance among junior runners and students, which prompted us to address it in this research.The researcher used the experimental method due to its suitability for the nature of the research. The research sample was deliberately selected, and its number reached (6) individuals. The most important results were:1-The training curriculum prepared by the researcher had a clear impact on developing the research sample's performance in the 400m freestyle. The training curriculum was appropriate for developing the characteristic of "speed endurance," which led to improved performance.